Define Intervention (The Biblical archaeology review, 2023)
What are Pseudepigrapha? 1. Texts with false attributions 2. Forged Moabite artifacts 3. Anonymous sculptures 4. A collection of Greek curses 5. The fear of plagiarism Answer: (1) Texts with false attributions Pseudepigrapha are texts whose named authors are not the real authors. They are usually attributed to famous or authoritative figures of a distant past, such as Enoch from […]